A Survey On Burnout And Related Factors Among Occupational Therapists In Iran - Mina Mozayan; Mehdi Rezaee; Mino Kalantari; Seyed Mehdi Tabatabaee (Shahid Beheshti University of Medical Sciences, 2012)
Background and Aim: High levels of job stress experienced over time, as well as personal frustration and inadequate coping skills, can lead to the syndrome known as burnout. In it has been shown in several surveys that high job stress in occupational therapists could lead to the burnout syndrome. Since few studies have been conducted in Iran concerning burnout in occupational therapists, we felt the necessity of performing this study to make Iranian therapists more aware of the syndrome and its related factors.Materials and Method: A cross sectional survey was carried out on 87 Iranian occupational therapists in the current study. A questionnaire consisting of two parts (demographic dates & maslach burnout inventory) was sent to all therapists who were members of medical organization.Results: 80.4% of therapists reported mild to moderate symptoms of burnout, while nobody has reported severe burn out. Low job satisfaction (P value=0.038) and job experience less than 5 years (P value=0.049) were the two variables associated significantly with burnout.Conclusion: In the present study high rate prevalence of burnout shows that occupational therapists in Iran are not in a good health state and it can indicate that Iran health system should pay more attention to this group. According to our study the early years of a therapist's carrier are the period when the therapist is at risk of burnout. So we believe that students should be given more information about burnout syndrome and its coping mechanisms during their education at the university.